Are the Early Postoperative Outcomes of Coronary Artery Bypass Grafting Surgery in Elderly Women Worse Compared to Men's? - Yüksel,Ahmet (2017)
Abstract Objective: To investigate the impact of gender difference in early postoperative outcomes in elderly patients (aged 70 or older) undergoing coronary artery bypass grafting surgery. Methods: Between October 2009 and December 2013, a total of 223 elderly patients (aged 70 or older) undergoing isolated primary coronary artery bypass grafting surgery were included in this retrospective observational cohort study. Patients were divided into two groups according to their gender. The patients' medical records were collected, their baseline preoperative characteristics, operative data, and postoperative outcomes were retrospectively reviewed, and the effect of gender difference in the early postoperative outcomes was analyzed. Results: Group 1 (female patients) and Group 2 (male patients) consisted of 71 and 152 patients, respectively. Mean age of patients was 74.4±3.6 years (range: 70-84 years). The level of EuroSCORE I, the incidence of hypertension and hyperlipidemia were significantly higher in Group 1, while the rate of smoking was significantly higher in Group 2. Mean postoperative intubation time, length of intensive care unit and hospital stay were longer in female patients than in male patients, but these differences were not statistically significant. No statistically significant difference between two groups in terms of the transfusion of blood products was observed. The rates of in-hospital mortality and major postoperative complications were statistically similar between the two groups. Conclusion: In conclusion, the female gender was not associated with worse early postoperative outcomes in elderly patients undergoing coronary artery bypass grafting surgery.